Psychometric Properties of Working Memory Test for Cycle Two (Grades 5-7) of Basic Education in Muscat Governorate in Oman - Faiza G. Albalushi; Rashid S. Almehirzi; Abdulqawi S. Al Zubaidi (Sultan Qaboos University, 2018)
The study aimed to develop a test to measure working memory for students in grades 5-7 in Basic Education and examine its psychometric properties. The study aimed also to develop the required norm scores for score interpretation. The sample consisted of 300 male and female students from grades  5, 6 and 7 in Muscat governorate. The validity of the working memory test was examined through face validity, construct validity, predictive validity and concurrent validity. The results supported the validity of the test. Confirmatory factor analysis showed the fit of data to the factorial structure of the working memory. In addition, the test showed high predictive validity of student achievement for several subjects. The reliability of the test was examined using Cronbach alpha reliability and test-retest reliability. Cronbach Alpha reliability ranged between 0.62 and 0.86 for the three grades. Similarly, test-retest reliability was between 0.35 and 0.75. The norm scores were computed using standardized scores and percentile ranks for each of the three subtests within each grade.